Bacteriological evaluation of bladder calculi: a study - Singh, Priyanka (International Journal of Research in Medical Sciences, 2018)
Background: Despite modern antibiotic therapy and technological advances in lithotripsy, the presence of infection in patients with urinary stones, as well as with infectious stones is still a significant cause of morbidity and mortality. Recent findings lend more theories as to how infection leads to stone formation. Methods: Bacteriological study was conducted on pre-operative urine and operated bladder stones. Pre-operative urine samples were collected aseptically for macroscopic and microscopic examination. Both pre-operative urine and operated renal stones were processed for bacteriological culture. The isolated microorganisms were identified by standard techniques. Results: Urinary tract infection was present in 27.88% cases. Majority of cases urine culture was positive (12.5%). E. coli was the commonest organism pseudomonas aerogenosa 3.84% klebsiella aureogenosa 1.92%, staphylococcus aureus and proteus 0.96% present in and mixed organism was found in 3.84% cases. Conclusions: This study revealed the following aspect: The incidence of urinary stone was higher in patient having predisposing factor: recurrent UTI, Urinary Stasis, Inadequent water intake, anatomical abnormality in urinary tract. The prepoderent microorganism found in stone and urine is E coli, followed by Pseudomonas aeruginosa, Staphylococcus aureus, Proteus.